Gereja kegembiraan & harapan : merayakan 45th Gaudium et spes - Riyanto, E. Armada, 1965-; Mistrianto; Vatican Council 1962-1965). (Deresan, Yogyakarta : Penerbit Kanisius, 2011)
Social role of Catholic Church in Indonesia according to Gaudium et spes document of the 2nd Vatican Council.
Includes bibliographical references.
Keywords: Catholic Church -- Indonesia; Church and social problems -- Indonesia -- Catholic Church